Integrated library system : the evolution / Halimatun Saidiah Mohamad and Syaza Aina Mat Adnan - Mohamad, Halimatun Saidiah; Mat Adnan, Syaza Aina (Faculty of Information Management, 2015)
This article will be discussed about the Integrated Library System (ILS). ILS is a software program to help library planning and manage their products and services. This ILS will make staff easy to manage their materials and enhance user's knowledge in using the software available such as OPAC. Other than that, in this article it will highlight about the most popular software being used worldwide which is Koha ILS. There will be list of the features of Koha ILS and the paradox in using the ILS. Koha ILS is full featured Integrated Library System and no cost for the license as long as it states the standard for open-source of ILS. Soy this article will focus on how it makes staff and users task more easily and brings benefits to them as long as the barriers when adapted to this ILS.